Expression of several deubiquitinase and tyrosine phosphatase genes involved in inflammatory response in lymphoma - Nguyen Hoang Giang; Nguyen Trong Ha; Nguyen Thi Xuan (Vietnam Journal of Science, Technology and Engineering, 2024)
Lymphoma represents a heterogeneous group of cancers affecting the lymphatic system, encompassing nonHodgkin lymphoma (NHL) and Hodgkin lymphoma (HL). The majority of NHL cases originate from B cells. HL is characterized by the presence of rare Hodgkin and Reed-Sternberg cells. Within the context of the inflammatory response, two SH2 domain-containing protein tyrosine phosphatases (SHPs), namely SHP-1 and SHP-2, serve as negative regulators. Deubiquitinating enzymes (DUBs) play a crucial role in inhibiting NF- κB activation in response to various stimuli. This study focuses on the DUBs OTUB1, OTUB2, and Cezanne. Blood samples were collected from 50 NHL patients, 26 HL patients, and 50 healthy individuals. Quantitative RT-PCR was employed to assess the mRNA expression of OTUB1, OTUB2, Cezanne, SHP-1, and SHP-2, while ELISA was used to determine IL-6 and CA125 concentrations. The results revealed that the mRNA level of OTUB1 was significantly downregulated in NHL patients but not in HL patients. Notably, Cezanne expression was downregulated in lymphoma patients, with significantly lower levels observed in HL compared to NHL patients. Furthermore, SHP-1 mRNA expression was significantly lower in the NHL group compared to the HL group or healthy individuals. Conversely, SHP-2 gene expression was upregulated in NHL patients but remained unchanged in HL patients. In conclusion, these findings highlight significant differences in the expressions of DUB and SHP genes and the inflammatory response in lymphoma patients. This study provides a foundation for further investigation into the roles of DUBs and tyrosine phosphatases in regulating the functional activation of lymphoma cells.